2004
DOI: 10.1007/s00705-004-0368-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the beak and feather disease viral genome indicates the existence of several genotypes which have a complex psittacine host specificity

Abstract: A study was made of the phylogenetic relationships between fifteen complete nucleotide sequences as well as 43 nucleotide sequences of the putative coat protein gene of different strains belonging to the virus species Beak and feather disease virus obtained from 39 individuals of 16 psittacine species. The species included among others, cockatoos ( Cacatuini), African grey parrots ( Psittacus erithacus) and peach-faced lovebirds ( Agapornis roseicollis), which were infected at different geographical locations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 36 publications
2
31
0
4
Order By: Relevance
“…start codon and TAA or TGA as stop codon; and ORF2, which codes for cp gene, was 750 nucleotides in length. The differences in the length of this gene in comparison with the data already published in the literature depend on the start codon that is chosen, since a canonical starting site is not evident (Bassami et al, 1998;de Kloet & de Kloet, 2004;Henriques et al, 2010). Within all of these genomes we identified three conserved amino acid motifs (FTLNN, GTPHLQGY and YCSK), a P-loop for dNTP binding (GPPGCGKS, amino acids 165 to 172) and three additional conserved motifs (WWDGY, amino acids 190 to 194; DDFYGWLP, amino acids 203 to 210; DRYP, amino acids 219 to 222) within the rep gene (Henriques et al, 2010), and the nuclear localization domain (RRRYARPxYRR RHIRRYRLRRRRHFRRRRFxTNRIYTLRxKRQ) on the N-terminus of the CP (Heath et al, 2006).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…start codon and TAA or TGA as stop codon; and ORF2, which codes for cp gene, was 750 nucleotides in length. The differences in the length of this gene in comparison with the data already published in the literature depend on the start codon that is chosen, since a canonical starting site is not evident (Bassami et al, 1998;de Kloet & de Kloet, 2004;Henriques et al, 2010). Within all of these genomes we identified three conserved amino acid motifs (FTLNN, GTPHLQGY and YCSK), a P-loop for dNTP binding (GPPGCGKS, amino acids 165 to 172) and three additional conserved motifs (WWDGY, amino acids 190 to 194; DDFYGWLP, amino acids 203 to 210; DRYP, amino acids 219 to 222) within the rep gene (Henriques et al, 2010), and the nuclear localization domain (RRRYARPxYRR RHIRRYRLRRRRHFRRRRFxTNRIYTLRxKRQ) on the N-terminus of the CP (Heath et al, 2006).…”
Section: Resultsmentioning
confidence: 95%
“…In these birds the infection was mainly restricted to Cacatua and Congo African grey parrots (CAGPs), indicating a high susceptibility to BFDV in these two species. Over the years, several classifications have been proposed by different authors (Ritchie et al, 2003;de Kloet & de Kloet, 2004;Heath et al, 2004;Varsani et al, 2011). Following the recent classification system proposed by Varsani et al (2011), the predominant strain circulating in Europe is BFDV-J, a strain isolated mainly from Psittacus erithacus.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are also no reports for other countries, such as Singapore and Indonesia, which act as the main bases of the bird trade and have many psittacine breeding farms. Therefore, it is necessary epidemiological studies including these countries, and molecular analyses to trace the roots of BFDV genotypes among countries and the relatedness between BFDV sequences and host species as in previous reports [5,6,8,15].…”
mentioning
confidence: 99%
“…Genomic analyses of BFDV have been advanced in recent years, and genetic diversity in ORF V1 and C1 has been also reported [2,5,6,8]. Epidemiological studies are still less than other studies, i.e., pathological or etiological studies, although some studies were recently reported in some countries [3,7,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation